Analysis of Rice Trade and Food Security in Southeast Asian Countries - Fadah, Isti; Lutfy, Cindy; Amruhu, Afwun (KnE Social Sciences, 2024)
The rice trade serves to maintain sufficient rice stocks to meet domestic country demands. The world’s main rice exporters and importers are located in the Southeast Asia region, so the volume change of traded rice can affect the flow of trade. Given the strategic importance of rice, numerous nations have stepped in to control the domestic rice market, to ensure political stability as well as food security. This article aims to examine how the rice trade has evolved in Southeast Asia with respect to food security. The study aims are addressed by the application of the descriptive analysis method. The findings indicate that from 110.5 million tones in 2010–2011 to 128.3 million tones in 2021–2022, Southeast Asian countries accounted for 1.22% of global rice imports, >22% of the world’s total rice consumption. In the meantime, the annual growth rate of rice exports was 3.3%. Over the past 10 years, ASEAN’s net rice exports have made up 53.3% of the world’s total and are expected to reach about 54.8%. Southeast Asian countries intervene in the rice market through international trade policies, both in the form of export bans and domestic rice price stabilization policies, to maintain rice stocks to strengthen the level of food security. Southeast Asia’s economic integration through the ASEAN Economy Community is an important moment to become the basis for achieving food security at the regional levels while at the same time making the rice market more open among Southeast Asian countries. Keywords: rice, trade, policy, Southeast Asia